“Elaboración de un jabón solido a partir de aceite de piñón blanco ( Jatropha curcas L.) en la Región San Martín - Marco Polo Arango Del Aguila (2014)
In the present investigation is disclosed the use of oíl Pinon Blanco (Jatropha curcas l.), with an index of acidity inappropriate for transesterification process; treated mixture with glycerine from biodiesel production, in a percentage of O, 5 and 10%, for preparing a salid soap, using the white oíl temperatures sprocket 50, 60 and 70 º C, for admission process and to determine their physical, chemical and organoleptic characteristics. This bi-factorial experimental nine (9) was obtained treatments, determining within the physical aspects; the rate of color formation and stability of foam, moisture, pH, consistency in water, bulk density and hardness, using analytical methods with laboratory equipment and materials, also to determine the chemical characteristics, the method of the technical standard was followed Peruvian to determine the rate of free alkali, total crude unsaponifiable matter and fatty acids, on the other hand by a sensory evaluation of appearance, odor,color and texture as a control was determined using two commercial wash soap. The results of the physical characteristics showed there effect of incorporation of glycerin, process temperature and the interaction of both on soap obtained from each treatment, while chemical analysis determined that all treatments are within the parameters required by the NTP for laundry soap. The results obtains of the sensorial analysis stated the treatments have been a less acceptation to different of the commercial soaps, however this deficient can be better with the incorporation of other compounds. In conclusion to make soap with white gear oil should not be used at temperatures above 50 º C and mixed with more than 5% glycerol treated and should be included in case you want to improve the amount of oil that allows foam to provide 12this feature soap.